A new sun moth species from the Flinders Ranges in South Australia (Lepidoptera, Castniidae) - Kallies, Axel; Edwards, Ted (Zootaxa, 2018)
Sun moths (Castniidae) constitute a small family of day-flying butterfly-like moths that have their centers of diversity in South America and Australia. Here we describe a new castniid from the Finders Ranges, South Australia. Synemon arkaroola spec. nov. is similar and related to Synemon brontias Meyrick, 1891 but differs by a number of external and genitalic characters, including the extensive bright orange markings on the hindwings. The new species inhabits dry creek beds and adjacent slopes where the hostplant, Scented Lemon Grass, Cymbopogon ambiguus (Hack.) A. Camus (Poaceae), grows.